Legal Protection of Creditors of Fiduciary Guarantee Holders for the Transfer of Fiduciary Guarantee Objects by Debtors - Redanti, Maya; Kusuma Dewi , Amelia Sri; Djumikasih (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
The transfer of fiduciary collateral objects by debtors without creditor approval is increasingly common due to the weakening economic conditions of debtors. This study aims to examine the legal protection for creditors holding fiduciary collateral against the transfer of collateral objects by debtors. The research method used is socio-legal research. The study finds a misalignment between existing laws and these legal events, leading to sanctions and criminal threats for debtors in breach. Creditors have the right to file lawsuits in the District Court against debtors for actions detrimental to the creditors. The study concludes that legal protection for creditors in fiduciary collateral transfer cases by debtors needs enhancement, both through regulatory improvements and by increasing the capacity of law enforcement to handle such cases.